Descemet membrane endothelial keratoplasty and refractive surgery. Issue 4 (July 2017) - Tong, C. Maya; Baydoun, Lamis; Melles, Gerrit R.J.
Abstract : Purpose of review: Descemet membrane endothelial keratoplasty (DMEK) has become a first-line treatment in corneal endothelial diseases because of its exceptional clinical outcomes and low complication rates. Because of its improved refractive predictability, DMEK is now also considered for managing cases with endothelial decompensation following previous refractive procedures, or in combination with those. This article reviews the clinical outcomes in these cases and discusses the possibility of refractive interventions following DMEK. Recent findings: DMEK has been successfully performed in eyes after laser in-situ keratomileusis, eyes after anterior chamber intraocular lens (IOL) implantation and aphakic eyes. Often, DMEK is combined with cataract surgery (triple-DMEK). Initial reports on reducing the refractive cylinder by toric IOL implantation are available. Although there are some reports on phacoemulsification and IOL implantation after phakic DMEK, reports on laser refractive procedures following DMEK are lacking. Summary: In contrast to earlier keratoplasty techniques, DMEK induces on average only mild refractive shifts owing to the 'natural' restoration of the cornea. As such, DMEK may be ideal in managing corneal decompensation in refractive patients. However, further studies are required to assess the safety and efficacy of DMEK after refractive treatment and of refractive procedures following DMEK.